Genetic analysis of early seedling vigour traits in advanced breeding lines of rice (Oryza sativa L.): Genetic analysis of ESV traits - Chennareddy, Ujwala; Priya, M Shanthi; Sreelakshmi, Ch; Umar, SN (ORYZA-An International Journal of Rice, 2025)
Sixty-four advanced breeding lines of rice, along with four checks, were evaluated to assess genetic variability parameters, correlations, path coefficients, and principal components. Variability studies revealed that root length, root-shoot ratio, and root dry weight recorded strong estimates of coefficients of variation at both the genotypic and phenotypic levels, as well as high heritability and genetic advance as a percentage of the mean. Correlation and path coefficient analyses showed a strong positive association between the first count of germination, seedling fresh weight, and seedling vigour index II, all of which also exhibited high positive direct effects on grain yield. Principal component analysis (PCA) indicated that the first five PCs together explained 81.70% of the total variability. The genotypes NLR 34417, NLR 20002, NLR 20022, NLR 33648, and NLR 33891 exhibited superior performance for both yield and early seedling vigour (ESV) traits. This dual advantage highlights their potential as promising candidates for further evaluation under direct-seeded cultivation conditions.